Spectroscopy and interactions of metal and metal cation complexes - Plowright, Richard J. (2010)
The work in this thesis looks at the spectroscopy and interactions of metals and metal cation complexes. There are two aspects of this vast subject that are considered: the electronic spectroscopy of Au-RG complexes and the ion-molecule chemistry of metals important in the mesosphere-lower thermosphere (MLT) region of the atmosphere.